Calcium regulates acid-sensing ion channel 3 activation by competing with protons in the channel pore and at an allosteric binding site. Issue 12 (21st December 2022) - Roy, Sophie; Johner, Niklaus; Trendafilov, Viktor; Gautschi, Ivan; Bignucolo, Olivier; Molton, Ophélie; Bernèche, Simon; Kellenberger, Stephan
Abstract : Abstract : The extracellular Ca 2+ concentration changes locally under certain physiological and pathological conditions. Such variations affect the function of ion channels of the nervous system and consequently also neuronal signalling. We investigated here the mechanisms by which Ca 2+ controls the activity of acid-sensing ion channel (ASIC) 3. ASICs are neuronal, H + -gated Na + channels involved in several physiological and pathological processes, including the expression of fear, learning, pain sensation and neurodegeneration after ischaemic stroke. It was previously shown that Ca 2+ negatively modulates the ASIC pH dependence. While protons are default activators of ASIC3, this channel can also be activated at pH7.4 by the removal of the extracellular Ca 2+ . Two previous studies concluded that low pH opens ASIC3 by displacing Ca 2+ ions that block the channel pore at physiological pH. We show here that an acidic residue, distant from the pore, together with pore residues, controls the modulation of ASIC3 by Ca 2+ . Our study identifies a new regulatory site in ASIC3 and demonstrates that ASIC3 activation involves an allosteric mechanism together with Ca 2+ unbinding from the channel pore. We provide a molecular analysis of a regulatory mechanism found in many ion channels.